The athlete's heart: A contemporary appraisal of the 'Morganroth Hypothesis' - Naylor, L. H.; George, K.; O'Driscoll, G.; Green, D. J. (Sports Medicine, 2008)
As early as 1975, Morganroth and colleagues hypothesized that the cardiac morphological adaptation observed in athletes corresponded with the nature of the haemodynamic stimulus imposed on the ventricles during repeated exercise bouts. Endurance training purportedly leads to an eccentric form of cardiac hypertrophy, principally characterized by increased left ventricular (LV) cavity dimension, and thus LV mass (LVM), as a consequence of prolonged repetitive volume overload. In contrast, strength training is supposedly associated with a concentric form of hypertrophy where increased ventricular wall thickness, with no change in cavity size, underpins the elevated LVM as a consequence of the pressure overload produced during strenuous resistive exercise. The 'Morganroth hypothesis' has been broadly adopted in the scientific and medical literature, partly as a consequence of a large body of cross-sectional evidence suggesting that endurance athletes have greater cavity dimensions than control subjects or resistance athletes. However, in conflict with the 'Morganroth hypothesis', several studies suggest that LV wall thickness is increased more in endurance-, than strength-trained athletes and others have reported no morphological changes in resistance-trained athletes. Such controversial data may reflect variability in the training stimuli, with little obvious attempt to quantify these issues in previous research. Further reflection on the 'Morganroth hypothesis' may also be pertinent as more sensitive technologies, such as magnetic resonance imaging, are now being employed for the assessment of cardiac morphology. Finally, the process of scaling (or normalizing) cardiac size for between-subject differences in body size and composition has further complicated the description and understanding of cardiac morphology in athletes. Specifically, it is possible that the increased LVM observed in some athletes may merely reflect a 'larger than normal' body size. These considerations emphasise the limitations of the predominance of cross-sectional comparisons in the available literature, which assume that differences between groups are due to a training effect per se rather than other between-subject differences. The small number of longitudinal training studies undertaken in athletes suggest that individuals with athlete's heart can exhibit further cardiac adaptation in response to training resumption. Longitudinal training studies undertaken in previously sedentary subjects generally indicate that exercise results in enlargement of LV cavity size, increases in wall thickness or LVM following training. However, there are currently limited longitudinal data available to comment on the effects of different modalities of exercise training on LV cavity dimension and wall thickness. In summary, significant caveats related to cross-sectional literature, the relative insensitivity of echocardiographic measurements and the paucity of evidence from longitudinal exercise training studies, warrant ongoing research to verify the 'Morganroth hypothesis'.